ANALISIS PENGARUH STRUKTUR KEPEMILIKAN SAHAM TERHADAP KEBIJAKAN HUTANG PERUSAHAAN - Azmi, Fika (PRESTASI, 2014)
Â AbstractÂ The purpose of this research is to analyze an impact of ownership structure (insiders ownership, shareholders dispersion, and institutional investors) on corporate debt policy in an agency theory context. Dividend payments, growth opportunities, firm size, asset structure, firm profitability and tax rate are control variables. This research is based on the previous research by Mohâd et al. (1998) that ownership structure (insiders ownership, shareholders dispersion and institutional investors) are important to explain corporate debt policy in an agency theory. Samples in this research are manufacture industry in Indonesia Stock Exchange during year 2010 to 2013 with purposive sampling method and obtain 40 company in manufacture industry. Collecting data is done by using pooling method and obtain 160 company in the observation years. The result of the research indicate that institutional investors have impact significant with negatif determinant on corporate debt policy. Insiders ownership and shareholders dispersion are insignificant with a negatif and positif determinant on corporate debt policy. Â Keywords: ownership structure, insiders ownership, shareholders dispersion, institutional investors, debt policy, agency theory.